Ternary chlorate heat storage material with heat storage performance and corrosivity and preparation method of ternary chlorate heat storage material
By adding nanoparticles to the ternary chloride salts of sodium chloride, potassium chloride and magnesium chloride, the problems of poor thermal conductivity and strong corrosion properties of the molten chloride salt are solved, and the heat storage density and corrosion resistance are improved. They are suitable for High temperature concentrated solar power generation system.
Patent Information
- Application Number
- CN202411258287.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-09
- Publication Date
- 2024-12-13
- Estimated Expiration
- 2044-09-09
AI Technical Summary
The existing molten chloride salts have poor thermal conductivity, low heat storage density and strong corrosiveness in high temperature environments, which limit their application in concentrated solar power generation systems.
By adding Al2O3, MgO, and Mg nanoparticles to the ternary mixed molten salt of traditional sodium chloride, potassium chloride and magnesium chloride, the microstructure of the molten salt is changed, the thermal conductivity and corrosion resistance are improved, and the thermal conductivity and corrosion resistance are improved, and the heat storage tank is based on The consumption of nanoparticles is supplemented.
It significantly improves the thermal stability and heat storage density of chloride salt heat storage materials, reduces corrosion, enhances the service life of alloy structural materials, and is suitable for next-generation concentrated solar thermal power generation systems.
Smart Images

Figure CN119119973A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of heat storage materials and material anticorrosion, and in particular to a ternary chloride heat storage material having both heat storage performance and corrosivity and a preparation method thereof. Background Art
[0002] As a potential heat storage and heat transfer material, molten salt has the characteristics of high heat transfer coefficient, high energy storage density, good thermal stability and low production cost. It has broad application prospects in high-temperature industrial waste heat recovery, solar thermal utilization and nuclear energy.
[0003] Common molten salts include nitrates, carbonates and chlorides. Nitrates are weakly corrosive, have low viscosity and are low in cost. However, their thermal stability is relatively poor and they are easily decomposed in high temperature environments, which limits the application of nitrates under high temperature conditions. Carbonates have the characteristics of high melting point, large latent heat of phase change and low price. However, they have high viscosity in liquid conditions and are easy to clog pipes, so they are limited in their application in concentrated solar energy systems.
[0004] Compared with the above-mentioned molten salts, chloride salts have the advantages of high decomposition temperature, wide operating temperature range, abundant material sources and low cost. As solar thermal power generation systems develop towards high parameterization, the requirements for the operating temperature range of molten salts are gradually increasing. Mixed chloride salts are considered to be the most promising heat storage materials in the next generation of concentrated solar power generation systems. However, at present, mixed chloride salts used as heat transfer and heat storage materials still have problems such as low thermal conductivity, small specific heat capacity and strong corrosiveness.
[0005] Since mixed chloride salts generally have problems with low specific heat capacity and low thermal conductivity, they will cause problems such as low heat storage density, slow heat storage and release rate in the heat storage system. In addition, due to poor heat transfer, thermal stress problems will also occur, endangering the safety of the equipment. Therefore, improving the safety and working performance of the heat storage system depends on improving the thermophysical properties of molten salt. Adding metal and metal oxide nanoparticles to molten salts and changing the microstructure of molten salts is considered to be an effective way to enhance the heat storage / heat transfer performance of molten salts.
[0006] On the other hand, the strong corrosiveness of chloride salts to alloy materials is also a key issue that limits their further application in concentrated solar power generation systems. In molten chloride salts, due to the dissolution of oxides in the molten salts, the alloy will not form an oxide film to inhibit corrosion during exposure, so higher corrosion protection requirements are placed on the material. Methods for slowing down the corrosion of molten chloride salts on alloy materials mainly include adding corrosion inhibitors and alloy modification. For example, adding magnesium metal to molten chloride salts to neutralize corrosive components can significantly reduce the corrosion rate. Establishing a coating barrier with thermodynamic stability and corrosion resistance on the surface of the alloy to prevent the alloy from direct contact with molten chloride salts can also significantly reduce the corrosion rate, but these methods have problems such as complex operation and high cost.
[0007] Therefore, it is of great practical significance to propose a molten salt heat storage material with good heat storage performance, weak corrosiveness, simple preparation method and convenient operation. Summary of the invention
[0008] The present invention provides a ternary chloride salt heat storage material and a preparation method thereof that take into account both heat storage performance and corrosivity, thereby solving the problems of poor thermal conductivity, low heat storage density and strong corrosivity of existing chloride molten salts, and can be effectively applied to the field of energy storage technology in solar thermal power generation systems.
[0009] In order to solve the above problems, the solution adopted by the present invention is:
[0010] A ternary chloride salt heat storage material that takes into account both heat storage performance and corrosiveness, comprising:
[0011] Nanoparticles that enhance heat storage performance and weaken corrosion performance are added to the traditional ternary mixed molten salt of sodium chloride, potassium chloride and magnesium chloride, and the ternary chloride heat storage material is prepared by melt blending. The nanoparticles can be replenished at any time in the heat storage tank according to the consumption of the nanoparticles.
[0012] Preferably, the ternary molten salt is calculated by mass percentage, sodium chloride 14.0% to 18.0%, potassium chloride 36.0% to 40.0%, and magnesium chloride 46.0% to 50.0%. Within the mass percentage range, the chloride molten salt has good thermal stability and excellent thermophysical properties.
[0013] Preferably, the nanoparticles are one or more of Al2O3, MgO, and Mg nanoparticles. The types of the nanoparticles can not only enhance the thermophysical properties of the molten salt, but also improve the corrosion resistance of the molten salt. The particle size of the nanoparticles is 50.0-100.0 nm. The particle size range of the nanoparticles has the characteristics of high specific surface area, which improves the heat storage density of the molten salt. The microstructure of the molten salt is changed to improve the heat conduction efficiency. The addition amount is 8.0%-10.0% of the total mass of the ternary chloride salt heat storage material. The total mass range of the nanoparticles can effectively promote the formation of a corrosion protection layer and improve the corrosion resistance of the molten salt.
[0014] Preferably, the consumption of the nanoparticles is determined by measuring the content of the nanoparticles using a dynamic light scattering instrument.
[0015] As a preferred improvement of the present invention, the replenishing method is to automatically open the feeding port on the top of the heat storage tank when the mass of the nanoparticles is detected to drop to 80.0%, add new nanoparticles with a mass percentage of 20.0% of the total mass of the added nanoparticles into the heat storage tank, and continue stirring.
[0016] A preparation method of a ternary chloride salt heat storage material with both heat storage performance and corrosivity, comprising: taking a certain mass of different powdered single-component chloride salts and nanoparticles respectively and placing them in a drying oven to dry for a period of time; then, using an electronic balance to weigh the chloride salts and nanoparticles of each component according to the mass ratio; physically mixing and stirring the three chloride salts and the nanoparticles to obtain a composite chloride salt; then, placing the composite chloride salt in a Mabo furnace and heating it to a high temperature, and after it is completely melted, continuously stirring and maintaining a constant temperature for a certain period of time; finally, closing the Mabo furnace for cooling and solidification, taking it out, grinding and drying it, and obtaining a ternary chloride salt heat storage material with both heat storage performance and corrosivity.
[0017] Preferably, the mixing method of the composite chloride salt is to weigh the dried powdered single-component chloride salt according to 14.0% to 18.0% sodium chloride, 36.0% to 40.0% potassium chloride, and 46.0% to 50.0% magnesium chloride, respectively; then weigh nanoparticles accounting for 8.0% to 10.0% by mass of the total mass of the three chloride salts and the nanoparticles, and physically mix and stir the three chloride salts with the nanoparticles to obtain the composite chloride salt.
[0018] As a preferred improvement of the present invention, the heating temperature and constant temperature conditions are 700°C to 800°C, the continuous stirring time after melting is 1 to 2 hours, the constant temperature duration is 1 to 2 hours, and the cooling and solidification temperature is 20°C to 40°C.
[0019] As a preferred improvement of the present invention, the drying treatment refers to placing the single-component chloride salt or the composite chloride salt under constant temperature and ventilation conditions and drying it at a temperature of 100 to 120° C. for at least 20 hours.
[0020] As a preferred improvement of the present invention, the purity of the single-component molten salt of sodium chloride, potassium chloride and magnesium chloride is not less than 99%.
[0021] As a preferred improvement of the present invention, the purity of the nanoparticles is not less than 98%.
[0022] The nanoparticles described in the present invention are required to have stable chemical properties and not react with chloride molten salt systems or metal materials in the working environment. Al2O3 and MgO nanoparticles are more preferred solutions.
[0023] Taking into account the anti-corrosion effect and thermal properties of the nanofluid mixed molten salt, the mass percentage of the nanoparticles is 10.0% of the ternary chloride salt heat storage material.
[0024] The particle size of the nanoparticles is preferably 100 nm, and most preferably 50 nm, because nanoparticles with smaller particle sizes have a larger specific surface area and are easy to combine with metal oxides generated by corrosion to form a protective layer and inhibit the diffusion of corrosion elements.
[0025] The purity of nanoparticles is 99.9% at best. This is because high-purity nanoparticles usually have better crystal structure integrity and higher chemical stability, and are not easy to react chemically with other components such as oxidizing substances in molten salt, thereby accelerating the corrosion process.
[0026] During use, the molten salt of the present invention is usually in contact with conventional corrosion-resistant alloys in the art, including nickel-based alloys or iron-based alloys, specifically Inconel 625 nickel-based alloys.
[0027] Description of the invention principle:
[0028] Chloride molten salt has the characteristics of stable chemical properties and wide operating temperature range, and is the most promising heat storage material for concentrated solar thermal power generation systems in high temperature environments. However, the strong corrosiveness and relatively poor thermal properties of chloride molten salt seriously affect its application. The present invention prepares a ternary chloride salt heat storage material that takes into account both heat storage performance and corrosiveness by adding nanoparticles to ternary chloride molten salt, which can effectively solve the above problems.
[0029] Specific technical principle description:
[0030] Chloride molten salts contain corrosive impurities such as oxygen and water vapor in high temperature environments. Among them, water vapor will hydrolyze with hydrophilic chlorides in chloride salts, such as magnesium chloride, to produce basic magnesium chloride and hydrogen chloride and other substances; on the other hand, oxygen will oxidize some chloride ions in the molten salt to produce chlorine gas. In summary, the chloride molten salt system will have a combined effect of dissolution, oxidation and chlorination on the alloy. These corrosive impurities will accelerate the corrosion process of the alloy.
[0031] The present invention adds nanoparticles to a ternary chloride molten salt system with sodium chloride, potassium chloride and magnesium chloride as main components. When the corrosion process is in progress, the nanoparticles diffuse into the corrosion interface where the chloride molten salt and the alloy material are in contact, react with other corrosion products, and form a protective layer with strong chemical inertness, thereby blocking the diffusion of oxidizing gases.
[0032] At the same time, nanoparticles in the ternary chloride molten salt system have a larger surface area in contact with the molten salt, increasing the effective area of energy exchange, absorbing and storing more heat, increasing the specific heat capacity of the molten salt, and thus increasing the heat storage density. In addition, there is an interaction between nanoparticles and molten salt, which can improve the microstructure of the molten salt, forming an orderly and uniform arrangement structure, promoting heat transfer, and helping to improve thermal conductivity efficiency and specific heat capacity.
[0033] Compared with the prior art, the advantages of the present invention are as follows:
[0034] The ternary chloride salt heat storage material of the present invention takes into account both heat storage performance and corrosiveness. The preparation process is simple. The nanoparticles can be dispersed in the chloride molten salt and evenly mixed, heated, stirred, cooled, and ground to complete the process. It is easy to industrialize and mass-produce. It has strong adaptability. The preparation method is suitable for different types and particle sizes of nanoparticles, and the most suitable type of nanoparticles can be selected according to actual needs. It is easy to operate and can be replenished in the heat storage tank at any time according to the consumption of nanoparticles. The nanoparticles in the heat storage material can, on the one hand, enhance the thermal conductivity and specific heat capacity of the ternary chloride molten salt, and on the other hand, reduce the corrosiveness of the metal containers and pipelines of the ternary chloride molten salt pile, thereby increasing the service life of the alloy structural materials and reducing cost losses. In summary, the invention provides a reliable heat storage material for the next generation of concentrated solar thermal power generation systems. BRIEF DESCRIPTION OF THE DRAWINGS
[0035] In order to more clearly illustrate the technical solutions in the embodiments of the present invention or the prior art, the following briefly describes the drawings required for use in the embodiments or the prior art description. In the drawings:
[0036] Figure 1 A method for preparing a ternary chloride salt heat storage material that takes into account both heat storage performance and corrosivity;
[0037] Figure 2Schematic diagram of the anti-corrosion principle of adding nanoparticles;
[0038] Figure 3 Mechanism of thermophysical property enhancement by adding nanoparticles. DETAILED DESCRIPTION
[0039] In order to ensure that professionals in the field understand the characteristics of the present invention, the following basic explanations and definitions are given for the professional terms and expressions cited in the specification and claims.
[0040] The theories or mechanisms mentioned in the present invention, whether correct or not, should not limit the scope of the present invention.
[0041] In the present invention, all features defined in the form of numerical ranges or percentage ranges, such as numerical values, quantities, and contents, are only for brevity and convenience. Therefore, the description of numerical ranges or percentage ranges should be considered to have included and specifically disclosed all possible secondary ranges and individual values within the ranges.
[0042] In the present invention, unless otherwise specified, the words “include”, “comprises” and the like in the entire specification and claims should be interpreted as including rather than excluding; that is, the meaning is “including but not limited to”.
[0043] In the present invention, the technical features of all implementation schemes are not listed one by one. Therefore, as long as there is no logical contradiction in the combination of these features, the technical features of each implementation scheme can be combined arbitrarily, and all possible combinations are considered to be within the scope of the description of this specification.
[0044] The present invention is described in detail below with reference to specific embodiments.
[0045] Example 1: Figure 1 As shown, in this embodiment, a method for preparing a ternary chloride salt heat storage material that takes into account both heat storage performance and corrosiveness is provided, and the steps are as follows:
[0046] 1. Preparation of ternary chloride salt
[0047] Sodium chloride, potassium chloride and magnesium chloride powders were placed in a drying oven at 120°C for 20 hours to remove moisture from the chloride salts. After cooling to room temperature, the samples were weighed using a high-precision electronic balance according to a mass ratio of 15:39:46 and fully stirred to obtain a ternary chloride salt.
[0048] 2. Preparation of ternary chloride salt heat storage material
[0049] In a dry air environment, weigh 90.0g of ternary chloride salt, add 10.0g of Al2O3 nanoparticles with a particle size of 50nm, and stir evenly with a glass rod. Place the mixed chloride salt in a muffle furnace and statically heat it to 800℃ until all the solids melt, then continue to stir and keep warm for 2 hours to form a liquid with uniform components, cool to 20℃ and take it out, grind the solidified ternary chloride salt heat storage material into powder with a pestle, and place it in a drying oven at 120℃ for 20h to obtain a ternary chloride salt heat storage material that takes into account both heat storage performance and corrosiveness.
[0050] 3. Corrosion Test of Supplementary Nanoparticles
[0051] 100.0g of ternary chloride salt heat storage material containing nanoparticles was placed in a heat storage tank, heated to 700°C in a Mabo furnace, and maintained at the temperature for 48 hours. A dynamic light scattering instrument was used to detect the mass change of the nanoparticles in the heat storage tank. When the mass dropped to 8.0g, 2.0g of Al2O3 nanoparticles with a particle size of 50nm was added to the heat storage tank through the feed port, and the stirring device was started to ensure that the newly added nanoparticles were evenly mixed with the molten salt.
[0052] Example 2: Figure 1 As shown, in this embodiment, a method for preparing a ternary chloride salt heat storage material that takes into account both heat storage performance and corrosiveness is provided, and the steps are as follows:
[0053] 1. Preparation of ternary chloride salt
[0054] Sodium chloride, potassium chloride and magnesium chloride powders were placed in a drying oven at 100°C and dried for 25 hours to remove moisture from the chloride salts. After cooling to room temperature, the samples were weighed using a high-precision electronic balance at a mass ratio of 14:36:50 and fully stirred and mixed to obtain a ternary chloride salt.
[0055] 2. Preparation of ternary chloride nanothermal storage materials
[0056] In a dry air environment, weigh 90.0g of ternary chloride salt, add 10.0g of Al2O3 and Mg nanoparticles with a particle size of 100nm, and stir evenly with a glass rod. The mixed chloride salt is placed in a muffle furnace and statically heated to 750℃ until all the solids are melted, then stirred and kept warm for 2h to form a liquid with uniform components, cooled to 40℃ and taken out, the solidified ternary chloride salt heat storage material is ground into powder with a pestle, placed in a drying oven at 110℃ for 22h, and a ternary chloride salt heat storage material with both heat storage performance and corrosiveness is obtained.
[0057] 3. Corrosion Test of Supplementary Nanoparticles
[0058] 100.0g of ternary chloride salt heat storage material containing nanoparticles was placed in a heat storage tank, heated to 700°C in a Mabo furnace, and maintained at the temperature for 48 hours. A dynamic light scattering instrument was used to detect the mass change of the nanoparticles in the heat storage tank. When the mass dropped to 8.0g, 2.0g of Al2O3 and Mg nanoparticles with a particle size of 100nm were added to the heat storage tank through the feed port, and the stirring device was started to ensure that the newly added nanoparticles were evenly mixed with the molten salt.
[0059] Example 3: Figure 1 As shown, in this embodiment, a method for preparing a ternary chloride salt heat storage material that takes into account both heat storage performance and corrosiveness is provided, and the steps are as follows:
[0060] 1. Preparation of ternary chloride salt
[0061] Sodium chloride, potassium chloride and magnesium chloride powders were placed in a drying oven at 110°C for 22 hours to remove moisture from the chloride salts. After cooling to room temperature, the samples were weighed using a high-precision electronic balance in a mass ratio of 18:36:46 and fully stirred to obtain ternary chloride salts.
[0062] 2. Preparation of ternary chloride salt heat storage material
[0063] In a dry air environment, weigh 90.0g of ternary chloride salt, add 10.0g of Mg nanoparticles with a particle size of 50nm, and stir evenly with a glass rod. Place the mixed chloride salt in a muffle furnace and statically heat it to 800℃ until all the solids melt, then continue to stir and keep warm for 2 hours to form a liquid with uniform components, cool to 30℃ and take it out, grind the solidified ternary chloride salt heat storage material into powder with a pestle, and place it in a drying oven at 100℃ for 25h to obtain a ternary chloride salt heat storage material that takes into account both heat storage performance and corrosiveness.
[0064] 3. Corrosion Test of Supplementary Nanoparticles
[0065] 100.0g of ternary chloride salt heat storage material containing nanoparticles was placed in a heat storage tank, heated to 700°C in a Mabo furnace, and maintained at the temperature for 48 hours. A dynamic light scattering instrument was used to detect the mass change of the nanoparticles in the heat storage tank. When the mass dropped to 8.0g, 2.0g of Mg nanoparticles with a particle size of 50nm was added to the heat storage tank through the feed port, and the stirring device was started to ensure that the newly added nanoparticles were evenly mixed with the molten salt.
[0066] Example 4: Figure 1 As shown, in this embodiment, a method for preparing a ternary chloride salt heat storage material that takes into account both heat storage performance and corrosiveness is provided, and the steps are as follows:
[0067] 1. Preparation of ternary chloride salt
[0068] Sodium chloride, potassium chloride and magnesium chloride powders were placed in a drying oven at 100°C for 25 hours to remove moisture from the chloride salts. After cooling to room temperature, a high-precision electronic balance was used to weigh the samples according to a mass ratio of 14:40:46 and the samples were fully stirred and mixed to obtain a ternary chloride salt.
[0069] 2. Preparation of ternary chloride salt heat storage material
[0070] In a dry air environment, weigh 90.0g of ternary chloride salt, add 10.0g of MgO nanoparticles with a particle size of 100nm, and stir evenly with a glass rod. Place the mixed chloride salt in a muffle furnace and statically heat it to 700℃ until all the solids melt, then continue to stir and keep warm for 2 hours to form a liquid with uniform components, cool to 25℃ and take it out, grind the solidified ternary chloride salt heat storage material into powder with a pestle, and place it in a drying oven at 100℃ for 25h to obtain a ternary chloride salt heat storage material that takes into account both heat storage performance and corrosiveness.
[0071] 3. Corrosion Test of Supplementary Nanoparticles
[0072] 100.0g of ternary chloride salt heat storage material containing nanoparticles was placed in a heat storage tank, heated to 700°C in a Mabo furnace, and maintained at the temperature for 48 hours. A dynamic light scattering instrument was used to detect the mass change of the nanoparticles in the heat storage tank. When the mass dropped to 8.0g, 2.0g of MgO nanoparticles with a particle size of 100nm was added to the heat storage tank through the feed port, and the stirring device was started to ensure that the newly added nanoparticles were evenly mixed with the molten salt.
[0073] The ternary chloride salt heat storage material with both heat storage performance and corrosion resistance obtained in the above steps has a simple preparation process, which can be completed by dispersing the nanoparticles in the chloride molten salt, uniformly mixing, heating, stirring, cooling and grinding, and is easy to industrialize and mass produce; it has strong adaptability, and the preparation method is suitable for different types and particle sizes of nanoparticles, and the most suitable type of nanoparticles can be selected according to actual needs; it is easy to operate, and can be replenished at any time in the heat storage tank according to the consumption of the nanoparticles.
[0074] In the above embodiments, the heat storage performance of the thermophysical properties of the ternary chloride salt with the addition of nanoparticles is limitedly improved, and the thermal conductivity and specific heat capacity are increased by more than 5.0%; while the corrosiveness is limitedly reduced, and the mass loss of the nickel-based alloy is reduced by more than 10.0%.
[0075] The present invention adds nanoparticles to a ternary chloride molten salt system with sodium chloride, potassium chloride and magnesium chloride as main components. Figure 2 As shown, when the corrosion process proceeds, the nanoparticles diffuse into the corrosion interface where the chloride molten salt and the alloy material are in contact, react with other corrosion products, and form a chemically inert protective layer, thereby blocking the diffusion of oxidizing gases.
[0076] At the same time, nanoparticles in the ternary chloride molten salt system have a larger surface area in contact with the molten salt, increasing the effective area of energy exchange, being able to absorb and store more heat, increasing the specific heat capacity of the molten salt, and thus increasing the heat storage density. There is also an interaction between nanoparticles and molten salts, which can improve the microstructure of the molten salt, forming an orderly and uniform arrangement structure, promoting heat transfer, and helping to improve thermal conductivity efficiency and specific heat capacity, such as Figure 3 shown.
[0077] The above contents are merely examples and explanations of the present invention. Those skilled in the art may make various modifications, supplements or replace the specific embodiments described in a similar manner. As long as they do not deviate from the invention or exceed the scope defined by the claims, they shall fall within the protection scope of the present invention.
Claims
1. A ternary chloride salt heat storage material that takes into account both heat storage performance and corrosiveness, characterized in that: The heat storage material is prepared by adding nanoparticles with enhanced heat storage performance and weakened corrosion performance to a ternary mixed molten salt of sodium chloride, potassium chloride and magnesium chloride through a melt blending method to obtain a ternary chloride salt heat storage material; when in use, new nanoparticles are added to the heat storage tank at any time according to the consumption of the nanoparticles, and continuous stirring is performed.
2. The ternary chloride salt heat storage material having both heat storage performance and corrosiveness according to claim 1, characterized in that: The ternary mixed molten salt contains 14.0% to 18.0% sodium chloride, 36.0% to 40.0% potassium chloride and 46.0% to 50.0% magnesium chloride in terms of mass percentage.
3. The ternary chloride salt heat storage material having both heat storage performance and corrosiveness according to claim 1, characterized in that: The particle size of the nanoparticles is 50.0-100.0 nm, and the nanoparticles are one or more of Al2O3, MgO, and Mg.
4. The ternary chloride salt heat storage material having both heat storage performance and corrosiveness according to claim 1, characterized in that: The added amount of the nanoparticles is 8.0% to 10.0% of the total mass of the ternary chloride salt heat storage material.
5. The ternary chloride salt heat storage material having both heat storage performance and corrosiveness according to claim 1, characterized in that: The new nanoparticles are supplemented by automatically opening the feeding port on the top of the heat storage tank when the mass of the nanoparticles is detected to drop to 80.0%, adding new nanoparticles with a mass percentage of 20.0% of the total mass of the added nanoparticles into the heat storage tank, and continuously stirring.
6. The ternary chloride salt heat storage material having both heat storage performance and corrosiveness according to claim 1, characterized in that: The purity of the molten salts of single-component sodium chloride, potassium chloride and magnesium chloride is not less than 99%; the purity of the nanoparticles is not less than 98%.
7. The method for preparing the ternary chloride salt heat storage material having both heat storage performance and corrosiveness as claimed in any one of claims 1 to 6, characterized in that: The heat storage material is prepared by a melt blending method, and good dispersibility and compatibility are achieved by mixing chloride salts and nanoparticles together at high temperature. The specific preparation method is as follows: a certain mass of different powdered single-component chloride salts and nanoparticles are respectively placed in a drying oven for drying for a period of time; then, each component chloride salt and nanoparticle are respectively weighed according to the mass ratio using an electronic balance; the three chloride salts and nanoparticles are physically mixed and stirred to obtain a composite chloride salt; then, the composite chloride salt is placed in a Mabo furnace and heated to a high temperature, and after all of it is melted, it is continuously stirred and kept at a constant temperature for a certain period of time; finally, the Mabo furnace is closed for cooling and solidification, and after being taken out, it is ground and dried to obtain a ternary chloride salt heat storage material that takes into account both heat storage performance and corrosiveness.
8. The preparation method according to claim 7, characterized in that: The stirring method is pure mechanical stirring to mix the chloride salt and the nanoparticles evenly; the grinding method is to use a pestle to crush the solidified ternary chloride salt heat storage material into powder.
9. The preparation method according to claim 7, characterized in that: The heating temperature and constant temperature conditions are 700°C to 800°C, the continuous stirring time after melting is 1 to 2 hours, the constant temperature duration is 1 to 2 hours, and the cooling and solidification temperature is 20°C to 40°C.
10. The preparation method according to claim 7, characterized in that: The drying treatment refers to placing the single-component chloride salt or the composite chloride salt under constant temperature and ventilation conditions and drying it at a temperature of 100 to 120° C. for at least 20 hours.
Citation Information
Patent Citations
Particle-molten salt compound heat-transferring and heat-accumulating medium material and preparation method thereof
CN103756647A
Chloride nano molten salt heat transfer and storage medium as well as application and preparation method thereof
CN113004875A
Method for preparing high-temperature corrosion protection molten salt by modifying oxide nanoparticles
CN116814226A
Multi-component mixed molten salt heat storage material as well as preparation method and application thereof
CN117143572A
